2019
DOI: 10.1016/j.vetmic.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviruses in free-ranging Australian bearded dragons (Pogona spp.)

Abstract: Adenoviruses are a relatively common infection of reptiles globally and are most often reported in captive central bearded dragons (Pogona vitticeps). We report the first evidence of adenoviruses in bearded dragons in their native habitat in Australia. Oral-cloacal swabs and blood samples were collected from 48 free-ranging bearded dragons from four study populations: western bearded dragons (P. minor minor) from Western Australia (n = 4), central bearded dragons (P. vitticeps) from central Australia (n = 2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…The newly discovered hosts include, among others, Mexican beaded lizard and gila, from each of which an isolated strain was obtained as well. From free‐living individuals, bearded dragons, anole lizards, and worm lizards, more reliable data can be deduced, which usually confirm a link between a certain host species and AdV type . The full genome of lizard AdV‐2, isolated from Mexican beaded lizard, was determined and the structure of the virion was also studied.…”
Section: Advs In Squamate Reptiles (Atadenovirus)mentioning
confidence: 99%
“…The newly discovered hosts include, among others, Mexican beaded lizard and gila, from each of which an isolated strain was obtained as well. From free‐living individuals, bearded dragons, anole lizards, and worm lizards, more reliable data can be deduced, which usually confirm a link between a certain host species and AdV type . The full genome of lizard AdV‐2, isolated from Mexican beaded lizard, was determined and the structure of the virion was also studied.…”
Section: Advs In Squamate Reptiles (Atadenovirus)mentioning
confidence: 99%
“…Virus yang dapat menginfeksi spesies Varanidae adalah Atadenovirus (Huminto & Agungpriyono 2008;Ball 2015) dan Varanid herpesvirus (Hughes-Hanks et al 2010;Wellehan et al 2005) (Tabel 1). Atadenovirus, salah satu genus dari adenovirus, merupakan virus patogen yang paling umum ditemukan pada reptil meliputi kadal dan ular (Ball 2015;Hyndman et al 2019;Pénzes et al 2020). Selain mudah ditemukan pada jenis kadal dan ular, virus ini juga terdeteksi pada berbagai spesies unggas (termasuk bebek) dan ruminansia serta marsupial (Pénzes et al 2020).…”
Section: Virusunclassified
“…However, inter-species transmission of squamate adenoviruses has occurred: Hyndman and Shilton (2011) and Benge et al (2019) have reported identical/near-identical adenovirus sequences from deeply divergent reptile species in Australia and the USA. Adenovirus infections have been reported in both healthy free-living and captive lizards (Kubiak 2013; Hyndman et al 2019;Szirovicza et al 2016) but have also been associated with morbidity and mortality in captive lizards: Seven wild-caught bark anoles (Anolis distichus), comprising five A. d. ravitergum and two A. d. ignigularis from the Dominican Republic, infected with an atadenovirus, died in captivity with clinical signs of gastroenteritis consistent with acute adenovirus infection (Ascher et al 2013) and a captive central netted dragon (Ctenophorus nuchalis) was found dead with an adenovirus infection in association with acute necrotising hepatitis (Hyndman and Shilton 2011). Adenoviruses have been detected in healthy captive bearded dragons (Pogona vitticeps) in the UK (Kubiak 2013) but have not been reported in free-living lizards in the UK.…”
mentioning
confidence: 99%